Hydrotalcite-like compound and noble metal monatomic self-assembled catalyst as well as preparation method and application thereof
Through the preparation method of hydrotalcite-like and precious metal single atom self-assembly catalyst, the problems of cumbersome process, low yield and high catalyst cost in isobutanol production are solved, and efficient and low-cost isobutanol production is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411530901.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the production process of isobutanol is cumbersome, the yield is low, the catalyst cost is high, and the use efficiency of precious metal catalysts is low, making it difficult to meet industrial production needs.
The preparation method of hydrotalcite-like self-assembly catalyst with precious metal single atoms is adopted, and the surface copper atoms are extracted by co-precipitation of copper-zinc-aluminum mixed salt solution and alkaline solution using organic complexing agent, and self-assembled with precious metal ions after calcination to form a G-CuZnAl-HTDO catalyst.
It reduces the amount of precious metals, reduces the preparation cost of catalysts, increases the selectivity and CO conversion rate of isobutanol, is suitable for industrial production, and solves the problems of harsh catalytic reaction conditions and carbon deposits.
Smart Images

Figure CN119524872A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical materials, and specifically relates to a hydrotalcite-like and noble metal single-atom self-assembly catalyst, a preparation method and an application thereof. Background Art
[0002] As an important organic chemical raw material, isobutanol is commonly used in pharmaceuticals, coatings and artificial rubber, etc. Its application involves many fields of the national economy and has an irreplaceable role. At the same time, because it has the advantages of high energy density and low hygroscopicity, it can also be used as a supplement or alternative fuel for gasoline, which can greatly reduce the emission of greenhouse gases and toxic tail gas. At present, the main method for generating isobutanol is propylene carbonyl synthesis, which has complicated process, low isobutanol yield and high price of catalyst used, resulting in isobutanol production cannot meet the current market demand. The product is mainly low-carbon alcohol, with complex composition and high separation cost. Precious metal catalysts have good effect in the reaction process of preparing isobutanol from synthesis gas, but precious metals are expensive. During the reaction process, the precious metal atoms in the bulk phase cannot play a catalytic role, affecting the use efficiency of the catalyst.
[0003] Lind Noora et al. used ZrO2 as a carrier to load multiple metals and obtained three catalysts: Rh-Co / ZrO2, Rh-Cu / ZrO2 and RhCuPd / ZrO2. Under the conditions of 225-300℃, 3MPa, and H2 / CO=2, the CO conversion rate was 58%, the ethanol selectivity was 38%, and the isobutanol selectivity was about 12%. The ratio of precious metal Rh:Co(Cu) in the catalyst was 1:5. The amount of precious metal used was large. From the perspective of industrial production, the catalyst cost was high, which was not conducive to industrial production.
[0004] Shiba Nothando C. et al. investigated the effect of different amounts of Ru added on Co-containing catalysts and found that Ru improved the reducibility and subsequent dispersion of Co sites, thereby improving the catalytic activity of H2 reduction catalysts. However, the addition of Ru inhibited the hydrogenation of CO in the synthesis gas reduction Co-Ru / SiO2 catalyst. The increase in the amount of Ru is beneficial to the formation of low-carbon alcohols. The CO conversion rate of the 15% Co-0.25% Ru / SiO2 catalyst was 15.2% and the selectivity of C2+ alcohols was 86.8% under the conditions of 350℃, 1MPa, and H2 / CO=2. The amount of precious metal Ru added to the catalyst is large, and the catalyst cost is high, which is not conducive to industrial production.
[0005] From the perspective of industrial production, precious metals are expensive. Although they have high catalytic activity in the preparation of low-carbon alcohols from synthesis gas, their scarcity makes it difficult to achieve large-scale industrial application. Summary of the invention
[0006] In view of the above problems, the present invention provides a hydrotalcite-like and noble metal single-atom self-assembly catalyst, a preparation method and an application thereof.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] The present invention provides a method for preparing a hydrotalcite-like and noble metal single-atom self-assembled catalyst, comprising the following steps:
[0009] Step 1, mixing a copper-zinc-aluminum mixed salt solution and an alkaline solution precipitant to obtain a suspension, then using an organic complexing agent to carry out a surface reaction, washing with an organic solvent to remove part of the surface copper atoms, and obtaining a copper-zinc-aluminum hydrotalcite precursor;
[0010] Step 2, calcining the copper-zinc-aluminum hydrotalcite precursor obtained in step 1 to obtain a copper-zinc-aluminum derived oxide rich in metal vacancies, and self-assembling the noble metal ions with the copper-zinc-aluminum derived oxide rich in metal vacancies to obtain the catalyst.
[0011] Furthermore, the molar ratio of copper ions, zinc ions and aluminum ions in the copper-zinc-aluminum mixed salt solution is 4:1:0.5 to 1:1:1.
[0012] Furthermore, the alkaline solution precipitant includes NaOH and Na2CO3, and the molar ratio of NaOH to Na2CO3 is 2:1 to 1:2.
[0013] Furthermore, the organic complexing agent is an organic small molecule containing nitrogen and sulfur, and its addition amount accounts for 0.2% to 5% of the solute mass in the copper-zinc-aluminum mixed salt solution. The organic complexing agent selectively extracts metal ions on the surface of hydrotalcite-like materials to achieve the regulation of the falling point of noble metal single atoms.
[0014] Furthermore, the organic complexing agent is one of methyl isosulfate, carbon disulfide and thiourea.
[0015] Furthermore, the organic solvent is one of ethanol, ether and ethylene glycol.
[0016] Furthermore, the specific conditions of the calcination are: the heating rate of the calcination temperature is controlled at 0.2-5°C / min, the calcination temperature is maintained at 300-400°C for 2-5h, and the helium purge rate is controlled at 10-30mL / min.
[0017] Furthermore, the self-assembly of the noble metal ions and the copper-zinc-aluminum-derived oxide rich in metal vacancies is specifically as follows:
[0018] The copper-zinc-aluminum derived oxide rich in metal vacancies is impregnated into a noble metal ion solution for 5-10 minutes, washed with distilled water and centrifuged, and dried at 60-80° C. to obtain the catalyst, wherein the noble metal ion includes one of rhodium ion, ruthenium ion and palladium ion, and the added amount of the noble metal ion is 0.005% to 0.05% of the mass of the copper-zinc-aluminum derived oxide rich in metal vacancies.
[0019] The present invention also provides a hydrotalcite-like and noble metal single-atom self-assembly catalyst, which is prepared by the above preparation method.
[0020] The present invention also provides an application of a hydrotalcite-like and noble metal single-atom self-assembled catalyst for catalytically synthesizing isobutanol using synthesis gas as a raw material.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. Hydrotalcite-like ions (HTLCs) are a type of layered inorganic material, which is mainly composed of a sandwich structure of positively charged metal oxides and interlayer balance anions. The oxide (HTDO) obtained after calcining hydrotalcite-like ions at a suitable temperature is a new type of highly efficient alkaline catalyst, and its structural feature is that it can retain the long-range order of the metal arrangement in the hydrotalcite-like ions. Usually, metal oxides present a structure of metal saturation coordination, and metal atoms cannot activate reactant molecules through chemical adsorption. The metal vacancy defects on the surface of hydrotalcite-like ions are electronegative, and they attract each other with positively charged noble metal cations through electrostatic forces, thereby realizing the self-assembly of HTDO and noble metal single atoms.
[0023] 2. The preparation method of the hydrotalcite-like and single-atom self-assembled catalyst provided by the present invention uses an organic small molecule complexing agent to directionally extract part of the copper atoms on the surface of the copper-zinc-aluminum hydrotalcite-like, and roasts to obtain a copper-zinc-aluminum hydrotalcite-like rich in metal vacancies, and self-assembles it with a small amount of precious metal ions to obtain a G-CuZnAl-HTDO catalyst, which reduces the amount of precious metals used, can be recycled and reused, has a low preparation cost, and is suitable for industrial production;
[0024] 3. The self-assembled G-CuZnAl-HTDO catalyst obtained by the present invention improves the efficiency of electron transfer, promotes the growth of carbon chain, is conducive to the reaction, and improves the conversion rate of carbon monoxide and the selectivity of isobutanol through the synergistic effect of active site Cu and co-catalyst Zn with precious metal ions;
[0025] 4. The self-assembled G-CuZnAl-HTDO catalyst provided by the present invention is suitable for catalytic synthesis of isobutanol using synthesis gas as raw material under mild conditions, which solves the problems of harsh catalytic reaction conditions, high production input cost and easy carbon deposition on the catalyst surface in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The figure is a flow chart of the preparation of the self-assembled G-CuZnAl-HTDO catalyst of the present invention;
[0027] Figure 2 Graphs showing the CO conversion rates of Examples 1, 2, 3, and 4;
[0028] Figure 3 Graph showing the selectivity of isobutanol for Examples 1, 2, 3, and 4. DETAILED DESCRIPTION
[0029] In order to further illustrate the technical solution of the present invention, the present invention is further described below through embodiments.
[0030] Example 1
[0031] The preparation method of a hydrotalcite-like and noble metal single atom self-assembled catalyst of the present embodiment comprises the following steps:
[0032] Weigh 2.00g Cu(NO3)2·3H2O, 0.61g Zn(NO3)2·6H2O and 0.39g Al(NO3)3·9H2O and dissolve them in 20mL distilled water to obtain a copper-zinc-aluminum mixed salt solution, in which the molar ratio of copper ions, zinc ions and aluminum ions is 4:1:0.5; use a mixed solution of NaOH and Na2CO3 as an alkaline solution precipitant, in which the molar ratio of NaOH to Na2CO3 is 2:1.
[0033] A co-precipitation method is adopted, and a copper-zinc-aluminum mixed salt solution and an alkaline solution precipitant are added into a reaction container at the same time. The copper-zinc-aluminum mixed salt solution is added into the reaction container at a rate of 60 drops / minute. The pH value of the reaction solution is controlled at 5.5 by adjusting the dropping speed of the alkaline solution precipitant to obtain a suspension. 0.06 g of carbon disulfide is titrated into the suspension. The suspension is crystallized in a hydrothermal autoclave at 100° C. for 5 hours to obtain a crystallized product. The crystallized product is washed with distilled water and filtered to neutrality, then washed with ethanol for 3 times, and vacuum dried at 70° C. for 8 hours. After drying, a copper-zinc-aluminum hydrotalcite precursor is obtained, which is expressed as CuZnAl-HTLcs.
[0034] The copper-zinc-aluminum hydrotalcite precursor was calcined, the heating rate of the calcination temperature was controlled at 1°C / min, the temperature was maintained at 360°C for 3h, and the purge speed was controlled at a helium flow rate of 10mL / min to obtain a copper-zinc-aluminum hydrotalcite-derived oxide catalyst rich in metal vacancies, represented as CuZnAl-HTDO. 3g of the copper-zinc-aluminum hydrotalcite-derived oxide catalyst rich in metal vacancies was placed in 0.15mg of rhodium ion solution (rhodium chloride), immersed for 5min, washed with distilled water and centrifuged, and dried at 60°C to obtain a self-assembled Rh-CuZnAl-HTDO catalyst.
[0035] The self-assembled Rh-CuZnAl-HTDO catalyst obtained above is used to catalyze the synthesis of isobutanol using synthesis gas as a raw material. The specific method is:
[0036] The catalyst was placed in a fixed bed and reduced at 300°C at a heating rate of 5°C / min for 2h in an atmosphere of N2:H2=3:1 (V / V).
[0037] The reduced catalyst and synthesis gas are used to react to obtain isobutanol: the synthesis reaction is carried out under the conditions of reaction temperature of 280° C., pressure of 3 MPa, and CO:H2=3:1 (V / V).
[0038] The GC9560 gas chromatograph was used for online testing, and the CO conversion rate was 49.57%. Figure 2 , hydrocarbons 10.14%, CO2 11.22%, total alcohol selectivity 78.64%; the alcohol distribution of methanol, ethanol, isopropanol, n-propanol, isobutanol, and n-butanol in the total alcohol is 30.91%, 37.23%, 1.96%, 4.51%, 25.77%, and 2.62%, respectively, and the selectivity of isobutanol is 25.77%, see Figure 3 .
[0039] Example 2
[0040] Weigh 1.34g Cu(NO3)2·3H2O, 0.83g Zn(NO3)2·6H2O and 0.83g Al(NO3)3·9H2O and dissolve them in 20mL distilled water to obtain a copper-zinc-aluminum mixed salt solution, in which the molar ratio of copper ions, zinc ions and aluminum ions is 2:1:0.8; use a mixed solution of NaOH and Na2CO3 as an alkaline solution precipitant, in which the molar ratio of NaOH to Na2CO3 is 1:1.
[0041] A co-precipitation method is adopted, and a copper-zinc-aluminum mixed salt solution and an alkaline solution precipitant are added into a reaction container at the same time. The copper-zinc-aluminum mixed salt solution is added into the reaction container at a rate of 60 drops / minute. The pH value of the reaction solution is controlled at 5.8 by adjusting the dropping speed of the alkaline solution precipitant to obtain a suspension. 0.015 g of methyl isosulfate is titrated into the suspension. The suspension is crystallized in a hydrothermal autoclave at 120° C. for 4 hours to obtain a crystallized product. The crystallized product is washed with distilled water and filtered to neutrality, then washed with ethanol for 3 times, and vacuum dried at 80° C. for 10 hours. After drying, a copper-zinc-aluminum hydrotalcite precursor is obtained, which is expressed as CuZnAl-HTLcs.
[0042] The copper-zinc-aluminum hydrotalcite precursor was calcined, and the calcination temperature was controlled at a heating rate of 0.5°C / min, and the temperature was maintained at 360°C for 4 hours. The purge speed was controlled at a helium flow rate of 15mL / min to obtain a copper-zinc-aluminum hydrotalcite-derived oxide catalyst rich in metal vacancies, represented as CuZnAl-HTDO. 3g of the copper-zinc-aluminum hydrotalcite-derived oxide catalyst rich in metal vacancies was placed in 0.30mg of ruthenium ion solution (ruthenium chloride solution), immersed for 8min, washed with distilled water, centrifuged, and dried at 80°C to obtain a self-assembled Ru-CuZnAl-HTDO catalyst.
[0043] The self-assembled Ru-CuZnAl-HTDO catalyst obtained above is used to catalyze the synthesis of isobutanol using synthesis gas as a raw material. The specific method is:
[0044] The catalyst was placed in a fixed bed and reduced at 320°C at a heating rate of 10°C / min for 3 hours in an atmosphere of N2:H2=2:1.
[0045] The reduced catalyst and synthesis gas are used to react to obtain isobutanol: the synthesis reaction is carried out under the conditions of reaction temperature of 320°C, pressure of 4 MPa, and CO:H2=2:1.
[0046] The GC9560 gas chromatograph was used for online testing, and the CO conversion rate was 51.74%. Figure 2 , hydrocarbons 9.85%, CO2 10.34%, total alcohol selectivity 79.81%; the distribution of methanol, ethanol, isopropanol, n-propanol, isobutanol, and n-butanol in the total alcohol is 41.14%, 16.13%, 2.07%, 4.96%, 32.93%, and 2.77%, respectively, and the selectivity of isobutanol is 22.93%, see Figure 3 .
[0047] Example 3
[0048] 1.79 g Cu(NO3)2·3H2O, 0.74 g Zn(NO3)2·6H2O and 0.47 g Al(NO3)3·9H2O were weighed and dissolved in 20 mL distilled water to obtain a copper-zinc-aluminum mixed salt solution, in which the molar ratio of copper ions, zinc ions and aluminum ions was 3:1:0.5; a mixed solution of NaOH and Na2CO3 was used as an alkaline solution precipitant, in which the mass ratio of NaOH and Na2CO3 was 1:2.
[0049] A co-precipitation method is adopted, and a copper-zinc-aluminum mixed salt solution and an alkaline solution precipitant are added into a reaction container at the same time. The copper-zinc-aluminum mixed salt solution is added into the reaction container at a rate of 60 drops / minute. The pH value of the reaction solution is controlled at 6.0 by adjusting the dropping speed of the alkaline solution precipitant to obtain a suspension. 0.12 g of thiourea is titrated into the suspension, and the suspension is crystallized in a hydrothermal autoclave at 125° C. for 3 hours to obtain a crystallized product. The crystallized product is washed with distilled water and filtered to neutrality, and then washed with ethanol for 3 times, and vacuum dried at 90° C. for 9 hours. After drying, a copper-zinc-aluminum hydrotalcite precursor is obtained, which is expressed as CuZnAl-HTLcs.
[0050] The copper-zinc-aluminum hydrotalcite precursor was calcined, the calcination temperature was controlled at a heating rate of 5°C / min, and the temperature was maintained at 380°C for 2h, and the purge speed was controlled at a helium flow rate of 30ml / min to obtain a copper-zinc-aluminum hydrotalcite-derived oxide catalyst rich in metal vacancies, represented as CuZnAl-HTDO. 3g of the copper-zinc-aluminum hydrotalcite-derived oxide catalyst rich in metal vacancies was placed in 1.50mg of palladium ion solution (palladium chloride solution), immersed for 10min, washed with distilled water, centrifuged, and dried at 70°C to obtain a self-assembled Pd-CuZnAl-HTDO catalyst.
[0051] The self-assembled Pd-CuZnAl-HTDO catalyst obtained above is used to catalyze the synthesis of isobutanol using synthesis gas as a raw material. The specific method is:
[0052] The catalyst was placed in a fixed bed and reduced at 400°C at a heating rate of 10°C / min for 3h in an atmosphere of N2:H2=3:2.
[0053] The reduced catalyst and synthesis gas are used to react to obtain isobutanol: the synthesis reaction is carried out under the conditions of reaction temperature of 400°C, pressure of 3Mpa, and CO:H2=1:1.
[0054] The GC9560 gas chromatograph was used for online testing, and the CO conversion rate was 55.16%. Figure 2 . Hydrocarbons 11.55%, CO2 12.76%, total alcohol selectivity 75.69%; the distribution of methanol, ethanol, isopropanol, n-propanol, isobutanol, and n-butanol in the total alcohol is 36.80%, 17.92%, 1.74%, 3.78%, 36.51%, and 3.25%, respectively, and the selectivity of isobutanol is 36.51%, see Figure 3 .
[0055] Example 4
[0056] Weigh 0.79g Cu(NO3)2·3H2O, 0.98g Zn(NO3)2·6H2O and 1.23g Al(NO3)3·9H2O and dissolve them in 20mL distilled water to obtain a copper-zinc-aluminum mixed salt solution, in which the molar ratio of copper ions, zinc ions and aluminum ions is 1:1:1; use a mixed solution of NaOH and Na2CO3 as an alkaline solution precipitant, in which the mass ratio of NaOH and Na2CO3 is 2:1.
[0057] A co-precipitation method is adopted, and a copper-zinc-aluminum mixed salt solution and an alkaline solution precipitant are added into a reaction container at the same time. The copper-zinc-aluminum mixed salt solution is added into the reaction container at a rate of 60 drops / minute. The pH value of the reaction solution is controlled at 6.2 by adjusting the dropping speed of the alkaline solution precipitant to obtain a suspension. 0.006 g of thiourea is titrated into the suspension. The suspension is crystallized in a hydrothermal autoclave at 130° C. for 3 hours to obtain a crystallized product. The crystallized product is washed with distilled water and filtered to neutrality, then washed with ethanol for 3 times, and vacuum dried at 100° C. for 8 hours. After drying, a copper-zinc-aluminum hydrotalcite precursor is obtained, which is expressed as CuZnAl-HTLcs.
[0058] The copper-zinc-aluminum hydrotalcite precursor was calcined, the heating rate of the calcination temperature was controlled at 3°C / min, the temperature was maintained at 350°C for 3h, and the purge speed was controlled at a helium flow rate of 20mL / min to obtain a copper-zinc-aluminum hydrotalcite-derived oxide catalyst rich in metal vacancies, represented as CuZnAl-HTDO. 3g of the copper-zinc-aluminum hydrotalcite-derived oxide catalyst rich in metal vacancies was placed in 0.60mg of rhodium ion solution (rhodium chloride), impregnated for 9min, washed with distilled water and centrifuged, and dried at 80°C to obtain a self-assembled Rh-CuZnAl-HTDO catalyst.
[0059] The self-assembled Rh-CuZnAl-HTDO catalyst obtained above is used to catalyze the synthesis of isobutanol using synthesis gas as a raw material. The specific method is:
[0060] The catalyst was placed in a fixed bed and reduced at 350°C at a heating rate of 10°C / min for 3h in an atmosphere of N2:H2=1:1.
[0061] The reduced catalyst and synthesis gas are used to react to obtain isobutanol: the synthesis reaction is carried out under the conditions of reaction temperature of 350° C., pressure of 5 MPa, and CO:H2=1:2.
[0062] The GC9560 gas chromatograph was used for online testing, and the CO conversion rate was 53.44%. Figure 2, hydrocarbons 9.72%, CO2 10.12%, total alcohol selectivity 80.16%; the distribution of methanol, ethanol, isopropanol, n-propanol, isobutanol, and n-butanol in the total alcohol is 28.67%, 35.68%, 1.23%, 3.78%, 28.45%, and 2.19%, respectively, and the selectivity of isobutanol is 28.45%, see Figure 3 .
[0063] The above shows and describes the main features and advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0064] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a hydrotalcite-like and noble metal single-atom self-assembled catalyst, characterized in that: The following steps are involved: Step 1, mixing a copper-zinc-aluminum mixed salt solution and an alkaline solution precipitant to obtain a suspension, then performing a surface reaction using an organic complexing agent, and washing with an organic solvent to obtain a copper-zinc-aluminum hydrotalcite precursor; Step 2, calcining the copper-zinc-aluminum hydrotalcite precursor obtained in step 1 to obtain a copper-zinc-aluminum derived oxide rich in metal vacancies, and self-assembling the noble metal ions with the copper-zinc-aluminum derived oxide rich in metal vacancies to obtain the catalyst.
2. The method for preparing a hydrotalcite-like and noble metal single atom self-assembled catalyst according to claim 1, characterized in that: The molar ratio of copper ions, zinc ions and aluminum ions in the copper-zinc-aluminum mixed salt solution is 4:1:0.5 to 1:1:
1.
3. The method for preparing a hydrotalcite-like and noble metal single atom self-assembled catalyst according to claim 1, characterized in that: The alkaline solution precipitant includes NaOH and Na2CO3, and the molar ratio of NaOH to Na2CO3 is 2:1 to 1:
2.
4. The method for preparing a hydrotalcite-like and noble metal single atom self-assembled catalyst according to claim 1, characterized in that: The organic complexing agent is an organic small molecule containing nitrogen and sulfur, and its addition amount accounts for 0.2% to 5% of the solute mass in the copper-zinc-aluminum mixed salt solution.
5. The method for preparing a hydrotalcite-like and noble metal single atom self-assembled catalyst according to claim 4, characterized in that: The organic complexing agent is one of methyl isosulfate, carbon disulfide and thiourea.
6. The method for preparing a hydrotalcite-like and noble metal single atom self-assembled catalyst according to claim 1, characterized in that: The organic solvent is one of ethanol, ether and ethylene glycol.
7. The method for preparing a hydrotalcite-like and noble metal single atom self-assembled catalyst according to claim 1, characterized in that: The specific conditions of the calcination are: the heating rate of the calcination temperature is controlled at 0.2-5°C / min, the calcination temperature is maintained at 300-400°C for 2-5h, and the helium purge speed is controlled at 10-30mL / min.
8. The method for preparing a hydrotalcite-like and noble metal single atom self-assembled catalyst according to claim 1, characterized in that: The self-assembly of the noble metal ions and the copper-zinc-aluminum-derived oxide rich in metal vacancies is specifically as follows: The copper-zinc-aluminum derived oxide rich in metal vacancies is impregnated into a noble metal ion solution for 5-10 minutes, washed with distilled water and centrifuged, and dried at 60-80° C. to obtain the catalyst, wherein the noble metal ion includes one of rhodium ion, ruthenium ion and palladium ion, and the added amount of the noble metal ion is 0.005% to 0.05% of the mass of the copper-zinc-aluminum derived oxide rich in metal vacancies.
9. The hydrotalcite-like and noble metal single atom self-assembled catalyst obtained by the preparation method according to any one of claims 1 to 8.
10. The use of the hydrotalcite-like and noble metal single atom self-assembled catalyst according to claim 9, characterized in that: Used to catalyze the synthesis of isobutanol using synthesis gas as raw material.